Staggered Price Setting and Endogenous Persistence - Robert Feenstra; Paul Bergin (University of California, Department of Economics, 1998)
This paper generates persistent effects of a monetary disturbance in the context of staggered price-setters. Previous research has been restricted by the CES functional form to price-setting rules that are constant markups over marginal costs. The present paper considers a translog form for preferences and an input-output structure for production in the context of a dynamic general equilibrium model of monopolistically competitive staggered price-setters. We derive a price-setting rule that is a function of milrginal cost and also competitors'' prices. This rule better captures the interaction of price-setters envisioned in Tajlor (1980) and Blanchard (1983) in their early work on staggered contracts. The model is able to generate reasonable persistence, and also confirms the conjecture of Taylor and Blanchard that increasing the number of contracting groups increases the degree of persistence.
Keywords: 330